The Task of "recycling-revitalization" as a Priority of Sustainable Development of Ukrainian Industrial Cities - Melnykova, Maryna; Boichenko, Mykola; Ragulina, Nadiia; Kocheshkova, Iryna (European journal of sustainable development, 2022)
Ukrainian industrial cities are characterized by a high level of technogenic load and pollution of the territory, which determines the priority of strengthening environmental safety in comparison with the other two components of sustainable development, ensuring social consensus and rational using of local resources. The environmental safety fortification actualizes the research of the processes of introducing of circular economy elements into production and restoration of urban territories which are occupied by industrial waste, i.e. solving the "recycling-revitalization" task in an industrial city. The general scientific and special methods of cognition have been used during the research. So, it allowed us to obtain the following results. The objective necessity and possibility of the "recycling-revitalization" task solving by Ukrainian industrial cities on the basis of the development and implementation of programs and projects, as well as the formation of eco-industrial parks has been substantiated. The experience of introducing of circular economy elements and ecological revitalization of the industrial cities’ territories in Europe and the United States has been analyzed including industrial symbiosis and powers in the environmental sphere of local governments. Three approaches to the management of industrial waste in the city have been considered: production-oriented, social-oriented, marketing-oriented. It has been determined that the production-oriented approach allows to form and implement of "recycling-revitalization" task solutions within the city. The organizational and economic solutions of "recycling-revitalization" task have been presented. The organizational solutions include coordinated interaction of enterprises of the city-forming, urban maintenance and urban planning sector in the management of industrial waste. Economic solutions to the “recycling-revitalization” task involve the using of three matrix models: a model of balanced resource allocation; assessing the impact of local indicators on the integral indicator of economic efficiency; model for accounting for uncertainty and risk factors. It has been argued that a socially-oriented and marketing-oriented approach to waste management in Ukrainian industrial cities presupposes concerted actions of participants at the regional and interregional level, which requires institutional and logistical support, which should be the subject of further research